Electric Vehicles in India : Identifying the Adoption Predictors - Attri, Rekha; Kushwaha, Pooja S. (Prabandhan: Indian Journal of Management, 2024)
Purpose : In this study, we explored the factors affecting Indian consumers’ willingness to adopt electric vehicles (EVs). Methodology : This study used the extended unified theory of acceptance and use of technology (UTAUT2) model to examine the factors impacting consumers’ desire to purchase electric vehicles. Data were gathered using a quantitative survey design from 518 prospective buyers of new fourwheelers, and SPSS was used for analysis. Findings : The study concluded that except for hedonic motivation and price value, all other determinants had an impact on the decision to purchase EVs. Implications : The findings of this study have significance for companies trying to enhance their communications to draw clients and encourage the use of EVs, given the increased attention on the usage of green technology globally. Originality : Our study explored the UTAUT2 factors along with risk perception and environmental concerns impacting EV adoption in the Indian context, which have not been previously reported. This study provided valuable insights for policymakers, manufacturers, and marketers striving to accelerate the transition to sustainable transportation.